Analysis of Solid Medical Waste Management at Uptd Regional General Hospital Datu Beru, Central Aceh Regency - Munadi Munadi; Thomson P Nadapdap; Ismail Efendy (PSPP JOURNALS, 2021)
The purpose of this study was to analyze the management of solid medical waste at a Regional Public Hospital. which includes minimization, sorting, separation, storage, transportation, destruction/final disposal of waste. The results of the study are that the management of solid medical waste in a Regional Public Hospital in general does not meet the requirements of the Minister of Health Regulation No. 7 of 2019 concerning Hospital Environmental Health, but there are several things that are already optimal, so it needs to be further improved. Lack of concern for waste producers, both health service providers, visitors and patients, which can trigger the mixing of solid medical waste with non-medical waste. It is recommended that waste management officers need to increase supervision and good cooperation with nurses and cleaners in separating medical and non-medical waste. Management pays more attention to facilities and infrastructure both regarding procurement and in the implementation process and pays attention to the availability of its human resources.